2020
DOI: 10.1108/jsbed-12-2019-0408
|View full text |Cite
|
Sign up to set email alerts
|

Examining the perceived value of extracurricular enterprise activities in relation to entrepreneurial learning processes

Abstract: PurposeThis study contributes towards increased understanding of the perceived value of extracurricular enterprise activities from an entrepreneurial learning perspective. Past decades have witnessed a global increase in the provision of enterprise and entrepreneurship education alongside a growing suite of extracurricular enterprise activities. However, there is a paucity of research examining how entrepreneurial learning might be understood in the context of these activities.Design/methodology/approachThe st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 83 publications
(167 reference statements)
2
31
0
2
Order By: Relevance
“…The type of entrepreneurship that the students take part in is quite different compared to research conducted on other co-curricular student venture creation (see, e.g. Pittaway et al, 2015;Preedy et al, 2020;Preedy and Jones, 2017). The case we have studied is an activity that is not within a course or program, directing it more towards the co-curricular stream of research as the students are connected with the industry and provided with some basic directions (e.g.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The type of entrepreneurship that the students take part in is quite different compared to research conducted on other co-curricular student venture creation (see, e.g. Pittaway et al, 2015;Preedy et al, 2020;Preedy and Jones, 2017). The case we have studied is an activity that is not within a course or program, directing it more towards the co-curricular stream of research as the students are connected with the industry and provided with some basic directions (e.g.…”
Section: Discussionmentioning
confidence: 95%
“…Another stream of research has focused more on student venture creation as a co-curricular activity. For instance, Preedy et al (2020) investigate student co-curricular activities and how students can learn in different ways through co-curricular activities. Pittaway et al (2015) research student clubs and highlight how students can gain important practical knowledge from being engaged in student entrepreneurship clubs.…”
Section: Student Venture Creationmentioning
confidence: 99%
See 1 more Smart Citation
“…These activities also help in developing leadership qualities and motivate the risk-taking attitude of students. This makes them courageous enough to endure challenges for their benefit and creativity, which in the long run can be seen as a positive sign toward entrepreneurship (Volkmann and Audretsch, 2017;Preedy et al, 2020). The universities are restructuring their settings to make them more congenial and in line with the objective of entrepreneurship.…”
Section: Co-curricular Activitiesmentioning
confidence: 99%
“…In today's era, entrepreneurship is one of the fastest-growing disciplines at universities and colleges. There is much focus on the practical implication and learning of entrepreneurship rather than just traditional wisdom (Preedy et al, 2020). On the other hand, students have reported that co-curricular activities help better understand these skills.…”
Section: Co-curricular Activitiesmentioning
confidence: 99%